Global Islamic Banking Development: A Review and Bibliometric Analysis Using R-Biblioshiny Application - Fahamsyah, Mohammad Hatta; Mawardi, Imron; Laila, Nisful; Shabbir, Malik Shahzad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Islamic banking refers to a banking system that operates based on the principles of Islamic law and Sharia. The bank is guided by Islamic economics and follows specific guidelines and principles that differentiate it from the conventional banking system. The aim of this article is to provide insight into the extensive bibliometric literature on Islamic banking globally. The method used in this study is a bibliometric analysis of the literature collected in 2014 to 2023 from Scopus database,te sample of the study is 69 of the 317 publications. This research classifies and visualizes them using R-Biblioshiny software. Overall, this review provides an appropriate reference point for further research on 'Islamic Banking Globally'. The results of the bibliometric analysis reveal that the research focuses mainly on ”Islamic” and “Bank”. The findings of this research show that Islamic banking globally has experienced a significant trend in the last 9 years and to be of significant interest for discussion and research. Notably, the density visualization analysis, which involves measuring the co-occurrence network of keyword pairs reveals a compelling trend, thus indicating that this research theme is still interesting to research today. However, further research is needed in more detail considering the increasing development of Islam.